Determinants of quality of life in psoriasis patients: A cluster analysis of 50 patients - Jaheersha Pakran; Najeeba Riyaz; G Nandakumar (Wolters Kluwer Medknow Publications, 2011)
Background: Although psoriasis generally does not affect survival, it certainly has a number of major negative effects on patients, demonstrable by a significant detriment to quality of life. Aims: We have done a study with the objective of assessing the clinical variables adversely affecting quality of life in patients diagnosed with psoriasis. Materials and Methods: This study is a cluster analysis of 50 consecutive consenting patients with psoriasis, of both sexes, aged over 18 years, attending the dermatology outpatient department of a tertiary care center. We measured the clinical severity using psoriasis area severity index and health-related quality of life using psoriasis disability index (PDI). Statistical analysis was performed using unpaired independent student's t-test, analysis of variance (and Scheffe's post hoc test as appropriate) and Pearson's correlation coefficients. Results: There was a significant correlation between the physician-rated severity of psoriasis and the extent of impact of psoriasis on physical disability as measured by the PDI. We have identified that a younger age at onset of disease and self-reported stress exacerbators suffer greater disability in most aspects of quality of life. Conclusions: On the basis of this study, we would recommend that psoriasis patients especially with severe disease require a more holistic treatment approach that encompasses both medical and psychological measures.